"Über den Ausgang des Heiligen Geistes": Eine Schrift eines anonymen Russen als Beilage im Brief von Simon Budny an Heinrich Bullinger vom 18. April 1563 - Bryner, Erich (Zwingliana, 2010)
Simon Budny (ca. 1530–1591) was a Reformed pastor who became a wellknown leader of the Anti-Trinitarian movement in Lithuania. In 1563, Budny wrote a letter to Heinrich Bullinger asking for his opinion on the filioque, which was the object of intense discussion in Lithuania. Budny enclosed a small work written by an anonymous Russian Orthodox author titled De processione Spiritus sancti that contains the main exegetical and theological arguments against the filioque (Zurich Staatsarchiv, E II 367, 231–242). This contribution includes an historical introduction, an edition, a German translation, and a text analysis. I propose that the anonymous author of this text may be the famous Russian theologian Maksim Grek (1470–1556) or one of his students, because the language, the content, the argumentation, the Biblical and Patristic proofs are similar to his Anti-Roman-Catholic works written between 1518 and 1525.